Implementasi Budaya Organisasi Islami Di Rumah Sakit Islam Yogyakarta PDHI Yogyakarta - Afrian Satria; Wijiharta Wijiharta (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2017)
This study aims to find out the implementation of Islamic values on organizational culture in Yogyakarta Islamic Hospital PDHI at every level of organizational culture according to the Schein (1991), ie artifact level, basic values and assumptions. Researchers conducted research through interviews, observation and documentation. Miles and Huberman analysis techniques (1992). In testing the validity of data with source of triangulation (Moleong, 2004). The results of the research indicate that the level of artifact organization culture, Islamic values are seen in company logo, vision and mission, room division, jargon and motto. At the level of values visible Islamic values on intentions because of God, trust, friendliness, and professionalism work, at the basic assumption level, Islamic values are visible in relation to the environment, human relationships with human and leadership functions.